2021
DOI: 10.2106/jbjs.cc.21.00129
|View full text |Cite
|
Sign up to set email alerts
|

Child Abuse with Thoracolumbar Fracture-Dislocation Treated with Pedicle Screw Fixation in a 2-Year-Old

Abstract: Case: A nonverbal 2-year-old boy presented with acute-on-chronic thoracolumbar fracture-subluxation with associated chylothorax and progressive neurologic dysfunction secondary to nonaccidental trauma. We discussed the successful management of this patient with short-segment pedicle screw instrumentation resulting in complete resolution of his chylothoraxes and neurologic impairment. A clinical follow-up is reported out to 12 months after hardware removal. Conclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
0
4
0
4
Order By: Relevance
“… Webb et al [ 17 ] 2020 1 29 months Fracture of the fourth lumbar (l4) vertebral body NA Child abuse NA Dead approximately two hours after arrival NA 11. Thornley et al [ 7 ] 2021 1 2 years Acute-on-chronic thoracolumbar fracture-subluxation Progressive neurologic dysfunction Child abuse Short-segment pedicle screw instrumentation 12 months Complete resolution of neurologic impairment …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… Webb et al [ 17 ] 2020 1 29 months Fracture of the fourth lumbar (l4) vertebral body NA Child abuse NA Dead approximately two hours after arrival NA 11. Thornley et al [ 7 ] 2021 1 2 years Acute-on-chronic thoracolumbar fracture-subluxation Progressive neurologic dysfunction Child abuse Short-segment pedicle screw instrumentation 12 months Complete resolution of neurologic impairment …”
Section: Discussionmentioning
confidence: 99%
“…In our case, a 2-year-old child suffered a fracture dislocation at the T12-L1 level from child abuse. Thornley P et al [ 7 ] reported a case of a 2-year-old boy child who suffered from thoracolumbar fracture-subluxation. They advocated their case as the first reported case of complete treatment, along with the consequent removal of hardware for a pediatric thoracolumbar fracture-subluxation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Se han publicado unos 50 casos de fracturas toracolumbares pediátricas, el 38% de ellas atribuidas a LNA en menores de dos años. 6,7 Lamentablemente, la omisión o el diagnóstico tardío afectan a más de un tercio de las víctimas. En este sentido, se han comunicado fracturas de huesos largos en un 77% y traumatismo craneoencefálico en el 50% de los casos.…”
Section: Introductionunclassified